Advanced monitoring in traumatic brain injury: microdialysis. Issue 2 (April 2017) - Carpenter, Keri L.H.; Young, Adam M.H.; Hutchinson, Peter J.
Abstract : Purpose of review: Here, we review the present state-of-the-art of microdialysis for monitoring patients with severe traumatic brain injury, highlighting the newest developments. Microdialysis has evolved in neurocritical care to become an established bedside monitoring modality that can reveal unique information on brain chemistry. Recent findings: A major advance is recent consensus guidelines for microdialysis use and interpretation. Other advances include insight obtained from microdialysis into the complex, interlinked traumatic brain injury disorders of electrophysiological changes, white matter injury, inflammation and metabolism. Summary: Microdialysis has matured into being a standard clinical monitoring modality that takes its place alongside intracranial pressure and brain tissue oxygen tension measurement in specialist neurocritical care centres, as well as being a research tool able to shed light on brain metabolism, inflammation, therapeutic approaches, blood–brain barrier transit and drug effects on downstream targets. Recent consensus on microdialysis monitoring is paving the way for improved neurocritical care protocols. Furthermore, there is scope for future improvements both in terms of the catheters and microdialysate analyser technology, which may further enhance its applicability.